Elevated levels of branched-chain amino acids have little effect on pancreatic islet cells, but L-arginine impairs function through activation of the endoplasmic reticulum stress response - Mullooly, N.; Vernon, W.; Smith, D.; Newsholme, Philip (Wiley-Blackwell, 2014)
New Findings - What is the central question of this study?: Recent studies have demonstrated strong correlations between circulating branched-chain amino acid (AA) levels and insulin resistance, a predictor of susceptibility to type 2 diabetes. This study investigated how elevations in various AA concentrations over a chronic incubation period affect rat pancreatic islet cell viability and insulin secretion. - What is the main finding and its importance?: We report that chronic exposure to specific AAs provoked islet cell toxic effects, particularly the insulinotropic AA l-arginine. Dose-dependent decreases in insulin secretion and cell proliferation were observed in addition to activation of the cell endoplasmic reticulum stress response. These results show, for the first time, that elevated l-arginine levels may impact negatively on islet function, providing further insights into ß-cell dysfunction in type 2 diabetes. - Recent metabolic profiling studies have identified a correlation between branched-chain amino acid levels, insulin resistance associated with prediabetes and susceptibility to type 2 diabetes. Glucose and lipids in chronic excess have been reported to induce toxic effects in pancreatic ß-cells, but the effect of elevated amino acid concentrations on primary islet cell function has not been investigated to date. The aim of this study was to investigate the effect of chronic exposure to various amino acids on islet cell function in vitro. Isolated rat islets were incubated over periods of 48 h with a range of concentrations of individual amino acids (0.1 µm to 10 mm). After 48 h, islets were assessed for glucose-dependent insulin secretion capacity, proliferation or islet cell apoptosis. We report that elevated levels of branched-chain amino acids have little effect on pancreatic islet cell function or viability; however, increased levels of the amino acid l-arginine were found to be ß-cell toxic, causing a dose-dependent decrease in insulin secretion accompanied by a decrease in islet cell proliferation and an increase in islet cell apoptosis. These effects were not due to l-arginine-dependent increases in production of nitric oxide but arose through elicitation of the islet cell endoplasmic reticulum stress response. This novel finding indicates, for the first time, that the l-arginine concentration in vitro may impact negatively on islet cell function, thus indicating further complexity in relationship to in vivo susceptibility of ß-cells to nutrient-induced dysfunction.